Can Green Finance and Digital Economy Foster Renewable Energy Development? Insight from G20 Countries with Two-Step-System-GMM Approach - Gunawan, Kleovan Nathanael (Purnomo Yusgiantoro Center, 2025)
The escalating concerns regarding environmental issues and the far-reaching implications of climate change have significantly intensified the focus on the shift towards renewable energy within academia and policymaking. This study investigates how the digital economy and green financing have affected the growth of renewable energy in G20 countries between 2010 and 2020. A key novelty of this research lies in examining the moderating effects of eco-innovation and institutional quality—factors often overlooked in prior studies. Using a dynamic panel data approach and the Two-Step System GMM (2SYSGMM) to address endogeneity concerns, our findings indicate that green finance and the digital economy play a positive role in fostering renewable energy development. The policy recommendations underscore the importance for G20 governments to prioritize investments in digital infrastructure to incorporate digital solutions into the energy sector and bolster the digital economy. Additionally, there is an emphasis on the need to promote innovation, literacy, and inclusivity in green finance, while advocating for the adoption of environmentally friendly technologies through robust research and development efforts and the strengthening of institutional frameworks. This study contributes to the literature by providing empirical evidence on how digital and financial mechanisms interact with institutional and innovation factors to accelerate the energy transition.